Palliative splenic irradiation in primary and post PV/ET myelofibrosis: outcomes and toxicity of three radiation schedules - Federico, Mario (PAGEPress Publications, 2009)
Splenectomy and splenic irradiation (SI) are the sole treatment modalities to control drug resistant splenomegaly in patients with myelofibrosis (MF). SI has been used in poor surgical candidates but optimal total dose and fractionation are unclear. We retrospectively reviewed 14 MF patients with symptomatic splenomegaly. Patients received a median of 10 fractions in two weeks. Fraction size ranged from 0.2–1.4 Gy, and total dose varied from 2–10.8 Gy per RT course. Overall results indicate that 81.8% of radiation courses achieved a significant spleen reduction. Splenic pain relief and gastrointestinal symptoms reduction were obtained in 94% and 91% of courses, respectively. Severe cytopenias occurred in 13% of radiation courses. Furthermore patients were divided in three groups according to the radiation dose they received: 6 patients in the low-dose group (LDG) received a normalized dose of 1.67 Gy; 4 patients in the intermediate-dose group (IDG) received a normalized dose 4.37 Gy; the remaining 4 patients in the high-dose group (HDG) received a normalized dose of 9.2 Gy. Subgroup analysis showed that if no differences in terms of treatment efficacy were seen among dose groups, hematologic toxicity rates distributed differently. Severe cytopenias occurred in 50% of courses in the HDG, and in the 14.3% and in 0% of the IDG and LDG, respectively. Spleen reduction and pain relief lasted for a median of 5.5 months in all groups. Due to the efficacy and tolerability of the low-dose irradiation 4 patients from the LDG and IDG were retreated and received on the whole 12 RT courses. Multiple retreatments did not show decremental trends in terms of rates of response to radiation nor in terms of duration of clinical response. Moreover, retreatment courses did not cause an increased rate of adverse effects and none of the retreated patients experienced severe hematologic toxicities. The average time of clinical benefit in retreated patients was much longer (21 months, range 44–10) than patients who were not retreated (5.75 months, range 3–6).